Paradigmas estratégicos de gestão da manufatura: configuração, relações com planejamento e controle da produção e estudo exploratório na indústria de calçados. - Godinho Filho, Moacir (Universidade Federal de São Carlos, 2001)
This work presents a new concept in Production Management field: Manufacturing Management Strategical Paradigms (MaMSPs). The main MaMSPs are identified: Modern Mass Production (MMP), Lean Manufaturing (LM), Responsive Manufacturing (RM), Mass Customization (MC) and Agile Manufacturing (AM). Relationships between these paradigms and manufacturing strategic goals and between the paradigms and important aspects o Production Control are proposed, providing a strategic approach to Production Management. Regarding each specific paradigm, this work reaches some important goals: it shows that Mass Production is still used in brazilian shoe industry, with some differences regarding Fordism. Relating LM, a literature review on this matter is structured according to four key elements of all MaMSP. Regarding RM, we propose a new methodology for design and implementation of RM. This methodology focuses on Production Control activities, which we consider the key to reach responsiveness. Regarding MC and AM we differentiate these paradigms. This differentiation contributes to diminish some concepts confusion about these paradigms. In this work we also propose two other methodologies: i) to identify the MaMSP used for a company; ii) to identify the most suitable MaMSP for a company. Both methodologies are illustrated in six case studies on brazilian shoe industry. Using both methodologies in a coordinated way provides a correct strategic position for companies. Finally, we conclude that this work contributes with Production Management field through the proposition of some methodologies regarding Manufacturing Strategy and Production Planning and Control.
Keywords: Administração da produção; Planejamento e controle da produção; Estratégia de produção; Indústria do calçado; ENGENHARIAS::ENGENHARIA DE PRODUCAO